Peran Orang Tua dalam Pendidikan Agama Anak di Era Digital - Tikasari, Putri Ariyatna (Maliki Interdisciplinary Journal, 2024)
Various aspects of human life are greatly influenced by technological advancements in the digital era, including children’s religious education. Parents play a very important role in building religious character and overseeing the filtering of information. How the role of parents in teaching religion to children amidst the rapid flow of digital information is the topic of discussion in this article. Education through habituation, example, advice and discussion, and rewards and punishments are some of the approaches used. This discussion shows how important the role of parents is in helping children understand religion in the modern era. Parents are expected to use technology wisely to support their children’s spiritual development.